The use of social media in business by women entrepreneurs in the KSA: The case of Instragram - Al-Haidari, Nawal Nasser (Department of Information Systems, 2017)
There have been few studies done on Small and Medium Enterprises (SME) in the context of the Kingdom of Saudi Arabia. Furthermore, studies show that Saudi women entrepreneurs (SWE) are constrained and faced with challenges that inhibit the growth of their small businesses. Such challenges include cultural factors, lack of business knowledge and expertise by entrepreneurs, lack of financial support for entrepreneurs, lack of training from the private sector, lack of business education supported by government for entrepreneurs and limited business opportunities. However, the adoption of social media, like Instagram, has been shown to help SME address numerous challenges experienced in their business context. The Instagram application has attracted huge numbers of users and is one of the fastest growing social media platforms in the world. It differentiates itself from other social networking sites by offering people a unique and easy way to communicate, since many social media users prefer posting photos or short video clips. Instagram is characterized by its primary function of posting and sharing images. Instagram is a highly effective, time-efficient, and user-friendly social media platform for businesses. Instagram quickly gained global popularity and reached roughly 300 million users in 2014. Thus Instagram, as a tool to market products and services, could enable SWE to overcome challenges which they face in the day to day running of their businesses. While the usefulness of adopting Instagram has been highlighted, there is limited knowledge regarding how SWE can adopt this social media application to overcome the various challenges experienced in their small businesses. No studies, to the author's knowledge, have examined this phenomenon in the Kingdom of Saudi Arabia (KSA). This study, therefore aims to examine how women entrepreneurs in the KSA adopt social media, Instagram in particular, to overcome various challenges in their small businesses. The study uncovers the challenges they face while adopting Instagram, as well as the advantages of adopting the tool. This study is qualitative, assumes an interpretive epistemological stance, and uses domestication theory as a framework for the research. Domestication theory involves looking at how people adopt technologies and integrate them into their activities and relationships in their daily lives. The data for this study was gathered through semi-structured interviews with a sample of 20 women entrepreneurs in the KSA. Interviewees were identified using snowball and purposive sampling techniques. Thematic analysis was used for analysing the data collected in order to extract codes and configurations of business challenges, Instagram-related challenges and benefits that result from adopting Instagram in small businesses. The findings revealed the following business challenges incurred by SWE: lack of business experience, stringent requirements for business registration, financial restrictions, judgement by society, the need for privacy and security, poor communication, and physical access to customers. The adoption of Instagram as a marketing space helped increase flexibility in the daily lives of SWE. The findings have shown that SWE appreciate the benefits of adopting Instagram in order to overcome business challenges. Yet, the findings also displayed that despite SWE still running their businesses through Instagram, there are a number of challenges that they are faced with. These challenges include coping with the lack of time to answer all inquiries, the lack of business rights and protection, the cancellation of orders, the need for uniqueness, and trust issues.